607 Risk Factors for Intraventricular Hemorrhage in Less than 32 Weeks Gestation Preterm Infants - Prospective Study. (October 2012) - Ognean, ML; Olariu, E; Boanta, O; Nicula, A; Gradinariu, G; Mutiu, I
Abstract : Chronic lung disease (CLD) of prematurity may complicate the postnatal development of the severe respiratory distress syndrome (RDS) and negatively affect the long term neurodevelopmental outcome of the premature infant. Aim: To evaluate the risk factors for CLD in ≤32 weeks gestation preterm infants. Methods: The study was developed in the Neonatology Dpt. of the Clinical County Emergency Hospital Sibiu between 01.01.2010–31.12.2011. The study group comprised 139 preterm infants with a mean GA of 30.26±1.93 weeks (24–32 weeks) and a mean BW of 1412.99±367.389g (600–2270g). The prospectively collected data were analysed using IBM SPSS 19.0 and were considered significant at a p<0.05. Results: CLD occurred with an incidence of 7.91% in the study group. The preterm infants that developed CLD had significantly lower GA (p 0.000), BW (p 0.000), and Apgar score at 1 minute (p 0.014). Significantly longer duration of the oxygen therapy (0.000), CPAP support (0.000), mechanical ventilation (p 0.003) and hospitalization (p 0.003) were found in those preterm infants that developed CLD compared with those without CLD. A significant association was found between CLD and apnea of prematurity, neonatal sepsis, nosocomial infection and ROP even after excluding deaths and outborn infants. Conclusions: Low GA, BW, the severity of RDS but also the presence of perinatal infection were the main risk factors identified in preterm infants with CLD.